농촌지역경제의 지속적 발전 전략 :지역균형발전을 통한 도농간 소득격차 완화방안(제3차 연도) - 박시현 (한국농촌경제연구원, 2006)
This is the third year report of the three-year collaborative research entitled “A Study on Mitigation of Income Gap between Urban and Rural Areas through the Balanced Regional Development Strategies.” This study is organized by the Korean National Research Council for Economics, Humanities and Social Sciences. The ultimate purpose of this study is to identify policy alternatives for reducing the income gap between rural and urban areas. The study consists of the following five parts: 1) development of agribusiness including food processing, local resource-based industry and agro-tourism in rural areas for the endogenous development of rural communities, 2) creation of social job opportunities in rural areas related to non-market attributes, public values and alternative public services of rural Korea, 3) development of manufacturing industry in rural areas, 4) vitalization of traditional rural markets, and 5) division of roles between the central and local governments. The results can be summarized as follows: 1) Since Korea’s rural economy depends largely on agriculture, agribusiness including food processing and agro-tourism is important in enhancing the rural income as it can increase the demand for raw materials and extend value-added processes. However, these sectors have faced difficulties in recent years due to disorganized promotion programs. In order to improve the rural economy, the following suggestions are made; include the ‘food and agro-tourism sector’ as part of an agricultural policy, enhance the relationships among food industry, tourism and agricultural sector, and develop industries like local food processing based on rural resources. In addition, the introduction of development programs by the characteristics of businesses (governing body, technology, raw materials, etc.) and the reformation of administrative systems are also suggested as policy alternatives. Agribusinesses such as food industry and green tourism must absorb local characteristics and historical attributes for sustainable development. Therefore, the most important thing is to seek for local characteristics and link them to a local resource-based industry as an endogenous industry. 2) The promotion of rural industrial clusters including the major region-based industries can also be an alternative to increase job opportunities for rural residents including farmers. Since agricultural resources like land are very limited in Korea, it is important to provide the opportunities to find jobs in non-agricultural sectors. According to a survey on the Rural Industrial Estate, the selection of business items that have strong relations with local areas is found to be one of the most important factors for success. Firms located in Gyeongsang-Do and Jeolla-Do were surveyed in this section in order to analyze how manufacturing industries in rural areas are operated and what kinds of polices they need. The results suggest that firms at first should try to develop items related to local resources, to improve relationship with regional strategic industries and to achieve agglomeration effects. Secondly, the introduction of a diversified support system and the transferring of infrastructure incentives to wage subsidies are also recommended. Finally, many firms should ask the government to ease various regulations on their management. 3) This section investigated the crisis which service industries in rural areas have faced and the causes of their decline. We also examined the theoretical and realistic adaptability of problems derived from government policies. The micro enterprises which play a central role in service industries of rural areas and the policies for the revitalization of conventional markets have been evaluated. The vitalization of the traditional rural market is another alternative for the sustainable development of rural economy. Normally, the rural market performs very important functions for the sustainment of local areas, such as buying daily commodities and selling agricultural products. However, most traditional rural markets have disappeared because of low rural population density, improved roads and transportation systems, and the rapid spread of modern supermarket chains in rural areas. Specialized programs for the rural market are proposed for the promotion of traditional rural markets based on a ‘choose and focus’ strategy. 4) The initiatives for job creation focus on social values of rural communities. The creation of various social job opportunities in rural areas is another suggestion to raise rural income because rural areas still have a large number of unemployed workers. The directions of commensurate strategies are as follows: i) various social work programs for rural areas are to be developed for job creation. ii) the initiatives of the programs should be taken by local governments instead of the central government. iii) the initiatives for job creation should be focused on the establishment of social enterprises, which may be pursued by a key planner who can learn to create social values in rural communities. iv) more emphasis should be given on regional social policies rather than regional development policies for the creation of good durable jobs in rural communities. The important thing in developing various social job programs is that the jobs should be based on local resources and be strongly attached to rural societies. In order to achieve the purpose of this suggestion, an area specific education project of a local government that sufficiently reflects the characteristics of a local area is more important than a central government policy. Especially, considering the demand in the market segment of LOHAS (Lifestyles of Health and Sustainability) through the paradigm shift from a regional development policy to a regional social policy is very important to this program. Moreover, the establishment of the Rural Social Job Creation Center is also suggested. 5) The division of roles between the central government and local governments is needed to operate efficiently policies related to rural economies and communities. The central government should adopt graduated national fiscal aid programs to undeveloped rural areas, consolidate various programs that are managed at several departments on rural development policies in order to avoid overlapping policies and improve efficiency, and find new policies that reflect the features and visions of future rural communities. The graduated national fiscal aid programs that apply to lower allotment rates on local governments’ shares of matching funds for less developed areas are recommended as an alternative for the improvement of rural economy. With respect to the financial analysis, the fiscal soundness of a local government affects strongly various regional development projects. Therefore, providing more financial support for the less developed areas through a graduated national fiscal aid system is reasonable in terms of balanced national development. As for local governments, a harmonious system for policy promotion, first, should be established to control well various programs and funds that come from various departments of the central government. Secondly, the local specific governance through the partnership between the private sector and a local government should be needed to develop local characteristics and creativeness. Thirdly, a local area should advance its relationship with other local areas and sometimes integrate with others for the sake of economies of scale and bargaining power. The cooperation among regions related to rural development is also important to promote the effective rural development. Finally, the local services should be provided to rural residents through the cooperation between the private sector and local governments. Researchers: Shi-Hyun Park, Dong-Phil Lee, Yong-Lyoul Kim, Joo-In Seong, Eun-Jung Shin, Kyung-Eun Choi, In-Woo Jun, Bong-Ho Shin, Yong-Ki Jung, Han-Sung Lee Research period: 2006. 1 - 2006. 11. E-mail address: shpark@krei.re.kr